Exploring the factors influencing the adoption of online medical services by older adults: a modified UTAUT2 based study - Huang, He; Zhu, Jiayi; Chen, Juhua; Qin, Yuxin; Chen, Shuguang (Frontiers in Public Health, 2025)
ObjectiveThe adoption rate of online medical services (OMS) among older adults remains notably low. Existing literature on OMS has rarely focused on older adults and the influences of individual characteristics within this population remain underexplored. To explore the factors influencing the adoption of OMS by older adults in China, this study proposes a modified Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model by integrating technology anxiety, trust, and perceived risk and adding new moderating variables such as education level and health status.MethodData was collected through a face-to-face survey, which included 379 valid questionnaires. Structural equation modeling (SEM) was used to analyze the data and test the research hypotheses.ResultsFor older adults, performance expectancy (β = 0.375, p < 0.001), effort expectancy (β = 0.244, p < 0.01), social influence (β = 0.198, p < 0.01), and trust (β = 0.237, p < 0.01) positively influence the usage intention of OMS, whereas technological anxiety (β = −0.129, p < 0.01) and perceived risk (β = −0.296, p < 0.001) negatively influenced the usage intention of OMS. No significant influence of facilitating conditions (β = 0.057, p = 0.293) or price value (β = 0.035, p = 0.721) on usage intention was found in this study. Meanwhile, the age, education level, and health status of the participants were found to moderate the effects of some major constructs on usage intention significantly.DiscussionOur empirical research discovers the drivers and barriers influencing the adoption of OMS by older adults. Based on the findings, we provide some recommendations to promote the adoption of OMS among older adults. Our findings and recommendations can aid providers, developers, policymakers, market practitioners, and managers of OMS in developing better services and strategies to successfully implement OMS among the older population.